Eureka [videorecording (DVD)] - Alonso, Lisandro; Casas, Fabián, 1965-; Caamaño, Martín, 1980-; Mortensen, Viggo, 1958-; Mastroianni, Chiara, 1972-; Clifford, Alaina (Film Movement, 2025)
"A cowboy arrives in a town in search of his daughter, a native policewoman arrests various offenders in a snowy landscape, while her niece, a basketball coach, reunites with her grandfather for a decisive journey that will shape her future, and a bird flies through time and space and begins to enter the minds and dreams of a native tribe in the Amazon jungle." -- Letterboxd.com, September 9, 2025.